Korzystanie z określeń nieostrych przy tworzeniu definicji legalnych w prawie podatkowym - Borszowski, Paweł (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego)
The study analyzed one of the significant problems in the creation of tax law. The consequences of this issue can be observed in tax practice. It is about creating legal definitions in tax law using vague terms in their normative shape. It is not an easy task for the legislator. On the one hand, it is about precisely defining the scope of the defined concept, and on the other hand applying a certain vagueness. Therefore, it is crucial to indicate the determinants of the use of vague terms as part of formulating legal definitions in tax law.
Keywords: vague terms; the legal definition in tax law; determinants